Impact of the NHS Stop Smoking Services on smoking prevalence in England: a simulation modelling evaluation. Issue 2 (5th April 2019) - Song, Fujian; Elwell-Sutton, Tim; Naughton, Felix
Abstract : Background: The English National Health Service NHS Stop Smoking Services (SSS), established in 2001, were the first such services in the world. An appropriate evaluation of the SSS has national and international significance. This modelling study sought to evaluate the impact of the SSS on changes in smoking prevalence in England. Methods: A discrete time state-transition model was developed to simulate changes in smoking status among the adult population in England during 2001–2016. Input parameters were based on data from national statistics, population representative surveys and published literature. The main outcome was the percentage point reduction in smoking prevalence attributable to the SSS. Results: Smoking prevalence was reduced by 10.8 % in absolute terms during 2001–2016 in England, and 15.3 % of the reduction could be attributable to the SSS. The percentage point reduction in smoking prevalence each year was on average 0.72%, and 0.11 % could be attributable to the SSS. The proportion of SSS supported quit attempts increased from 5.5 % in 2001, to as high as 18.9 % in 2011, and then reduced to 8.2 % in 2016. Quit attempts with SSS support had a higher success rate than those without SSS support (15.1% vs 11.3%). Smoking prevalence in England continued to decline after the SSS was much reduced from 2013 onwards. Conclusions: Approximately 15% of the percentage point reduction in smoking prevalence during 2001–2016 in England may be attributable to the NHS SSS, although uncertainty remains regarding the actual impact of the formal smoking cessation services.